Effect of variation in mesh size on trawl efficiency - Sitaramarao, J andKesavan Nair, A.K., Naidu, R.M., Ramarao, S.V.S. Narayanappa, G. Satyanarayana, A.V.V. (Fishery Technology, 2021)
Result of comparative fishing trials with a bulged belly design with three different mesh ranges in the body and wing to study the effect of mesh size difference on the performance of gear is discussed. While there is no significant difference in catch rate, predictably the 40 mm mesh size trawl fared wen when small sized fish like anchovies formed the major catch. The trawls with 60 and 80 mm mesh size gave better horizontal spread at a lower resistance showing savings in fuel.